1852 Del. Laws 664 - (:unkn) unknown (My University, 1852)
An Act To Incorporate the Town of Camden and for Other Purposes, ch. 652, § 3: Authorized the elected commissioners to regulate the discharge of guns or pistols.
Keywords: DISCHARGE